Resposta imunológica do tipo Th17 e sua repercussão clínica no lúpus eritematoso sistêmico - Souza Júnior, Edson Pereira de (2016)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease of unknown etiology characterized by disorders of immune responses to the antigens or specific constituents, consequent to genetic, hormonal and environmental factors. The objective is thus to early detect patients with lupus nephritis profile and identify the role of Th1, Th2 and Th17 responses in humans evaluating the use of immunomodulators as targeted therapy in autoimmune diseases. Levels of cytokines were assessed (IL-2, IL-4, IL-6, TGF-P, IL-10, IL-17, IFN-y and TNF-a) in patients diagnosed with systemic lupus erythematosus with renal impairment or with cutaneous-articular involvement (without nephritis) and healthy individuals who did not have autoimmune diseases, both female groups, aged 30-45 years in the period from March to October 2011. The average level of cytokines IL -10, IFN-y and IL-17 were higher in patients with lupus than in control group, whereas the levels of cytokines IL-2, IL-4, IL-6, TNF-a and TGF-P have demonstrated no statistical difference between these two groups. In addition, there was a statistically significant increase in levels of IFN-y and IL-17 in the subgroup of patients with lupus nephritis compared to the group of patients with cutaneous-articular involvement and to the control group. So, a better understanding of the cellular and molecular mechanisms involved in autoimmune diseases, especially SLE, may generate new prospects for treatment with the purpose of enabling intervention in the activation of specific ways of the inflammatory process with the aim of increasingly improve the quality of life of the patients.